Preparation method and application of double transition metal sulfide composite material coated with reduced graphene oxide

By reducing graphene oxide coated with double transition metal sulfide composite, the problems of low specific capacity, poor rate performance and short cycle life of the negative electrode material of potassium ion battery are solved, and high specific capacity and excellent electrochemical performance are achieved.

CN117766711BActive Publication Date: 2025-04-11JIANGSU UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311774495.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2025-04-11
Estimated Expiration
2043-12-21

AI Technical Summary

Technical Problem

The negative electrode materials of existing potassium ion batteries have lower specific capacity, poor rate performance and short cycle life.

Method used

The preparation method of reducing graphene oxide coated with double transition metal sulfide composite material (FeCoS@rGO) is adopted to obtain a bimetal oxide precursor through an oil bath, mixed and grinded, and calcined at high temperature under protective gas to obtain a bimetal transition metal sulfide, and then coated with graphene oxide.

Benefits of technology

The high specific capacity, excellent reversibility and cycle stability of the negative electrode material of the potassium ion battery are achieved, and the electrochemical performance is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117766711B_ABST
    Figure CN117766711B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of alkali metal batteries, and discloses a method for preparing a double transition metal sulfide composite electrode material coated with reduced graphene oxide and its application in the field of potassium ion batteries. Specifically, the following steps are included: dispersing a certain concentration of graphene oxide in deionized water, then dissolving two metal salts in the dispersion respectively, and obtaining a precursor in an oil bath under an alkaline environment; mixing and grinding the precursor with sublimated sulfur powder in proportion, and calcining at a high temperature under a protective gas to obtain a double transition metal sulfide composite material. The reduced graphene oxide-coated double transition metal sulfide composite material prepared by this method has abundant interface boundaries and a high ion diffusion rate. It is used for the negative electrode of potassium ion batteries and has excellent rate performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alkali metal ion batteries and relates to a method for preparing a double transition metal sulfide composite material FeCoS@C coated with reduced graphene oxide. Background Art

[0002] At present, lithium-ion batteries are widely used in portable electronic devices, power batteries, large-scale energy storage batteries and other fields due to their high operating voltage, high specific energy, long cycle life and other advantages. With the increasing social demand, the rising prices of raw materials have prompted researchers to find other alternatives. Potassium-ion batteries have similar working principles to lithium-ion batteries. Potassium resources are abundant, especially potassium has a redox potential (K) close to that of lithium. + / K: -2.93V vs standard hydrogen electrode (SHE)). As one of the alternatives to lithium-ion batteries, potassium-ion batteries have broad application prospects in the field of large-scale energy storage. The theoretical capacity of graphite negative electrode materials commonly used in lithium-ion batteries is only 279mAh / g in potassium-ion batteries, and the actual specific capacity is much lower than the theoretical value. In addition, the larger ionic radius of potassium ions can easily cause serious volume expansion of the graphite negative electrode, resulting in inactivation of the electrode material. Compared with carbon materials such as graphite, transition metal sulfides have higher theoretical capacity. As a type of negative electrode material for alkali metal ion batteries, they have the characteristics of rich raw material resources and stable structure. They are negative electrode materials for potassium ion batteries with great potential.

[0003] Metal sulfide negative electrode materials usually face problems such as large volume changes and fast capacity decay during the charge and discharge process. By introducing a second metal, the synergistic effect between the two metals can be used to alleviate the problems of capacity decay and low cycle life caused by volume expansion. In addition, the conductivity of metal sulfides can be improved by coating with carbon materials, while alleviating their volume expansion problem. Summary of the invention

[0004] The present invention provides a reduced graphene oxide coated double transition metal sulfide composite material (FeCoS@C) and a preparation method thereof. The main purpose is to solve the problems of low specific capacity, poor rate performance, short cycle life, etc. of current carbon-based electrode materials. The present invention provides a potassium ion battery negative electrode material that is safe and simple to prepare, has a regular morphology, and has good electrical conductivity. The designed negative electrode material has good cycle stability and ultra-high specific capacity.

[0005] The present invention relates to the preparation of a reduced graphene oxide coated double transition metal sulfide composite material (FeCoS@rGO). The method is characterized in that a double metal oxide precursor is obtained by oil bath, the precursor is mixed and ground with sublimated sulfur powder in proportion, and double transition metal sulfide is obtained by high temperature calcination under protective gas, and the double transition metal sulfide is coated with graphene oxide to synthesize a composite electrode material.

[0006] A method for preparing a reduced graphene oxide-coated double transition metal sulfide composite material comprises the following steps:

[0007] (1) fully ultrasonically dispersing graphene oxide in deionized water, and adding ammonia water to form an alkaline environment to obtain a graphene oxide dispersion;

[0008] (2) fully dissolving the iron salt and the cobalt salt in the graphene oxide dispersion, stirring at a certain temperature for a certain period of time, washing with deionized water and ethanol by centrifugation until neutral, and drying in an electric heating blast drying oven to obtain a black powder product precursor FeCoO for standby use;

[0009] (3) The black product precursor FeCoO and sublimed sulfur are mixed and ground evenly in proportion, placed in a porcelain boat, and heat treated at 140-170°C for 1-2 h under a protective gas atmosphere, and then continued to heat to 350-650°C for calcination for 2-3 h at a heating rate of 5°C / min; finally, a double transition metal sulfide composite material FeCoS@rGO coated with reduced graphene oxide is obtained.

[0010] In step (1), the concentration of the graphene oxide dispersion is 0.5-1 mg / mL, the volume ratio of ammonia water to deionized water is 1:9, and the ultrasonic time is 2 h.

[0011] In step (2), the total concentration of metal salts in the graphene oxide dispersion is 0.04 mol / L, wherein the molar ratio of Fe to Co is 1:1.

[0012] In step (2), the stirring temperature is 80-100° C. and the stirring time is 4 h.

[0013] In step (3), the mass ratio of the black product precursor to the sublimated sulfur is 1:0.5-1:4.

[0014] The reduced graphene oxide coated double transition metal sulfide composite material (FeCoS@rGO) prepared by the present invention has excellent electrochemical performance as the negative electrode of potassium ion battery. The specific performance is as follows:

[0015] (1) At a current density of 50 mA / g, the first discharge capacity of FeCoS@rGO reached 1616.6 mAh / g, the charge capacity was 604.6 mAh / g (about twice that of the graphite anode), and the first coulombic efficiency was 37.4%. After 45 cycles, its reversible capacity was still 479.5 mAh / g, showing excellent cycle performance.

[0016] (2) Rate performance test of FeCoS@rGO (such as Figure 1-10 ). At a current density of 50mA / g, the reversible specific capacity is 529mAh / g. When the current density gradually increases to 500mA / g, the reversible specific capacity is 166mAh / g, which is about 31% of the current density of 50mA / g. When the current density returns to 50mA / g, the reversible specific capacity returns to 517mAh / g, showing excellent rate performance.

[0017] The high-efficiency potassium ion battery negative electrode performance of the reduced graphene oxide-coated double transition metal sulfide composite material prepared by the present invention is due to:

[0018] (1) Synthesized FeCoS 4 Compared with other bimetallic sulfides, it has a higher metal valence and a higher sulfur content, and has a higher reactivity and a higher theoretical capacity.

[0019] (2) Zero-dimensional structure of FeCoS 4 It has a larger surface area, which is conducive to the infiltration of electrolyte and increases the electrochemical reaction area.

[0020] (3) Carbon-based material coating improves the conductivity of the electrode material and helps alleviate the volume expansion problem of sulfides during the cycle.

[0021] The beneficial effects of the present invention are:

[0022] (1) The present invention provides a potassium ion battery negative electrode material of reduced graphene oxide coated with double transition metal sulfide (FeCoS@rGO) and a preparation method thereof. The preparation method is easy to expand and is convenient for large-scale application.

[0023] (2) Compared with the existing bimetallic sulfide preparation method, the bimetallic sulfide structure in the reduced graphene oxide-coated bitransition metal sulfide composite material synthesized by the present invention is adjustable.

[0024] (3) Compared with the existing potassium ion battery negative electrode materials, the reduced graphene oxide-coated double transition metal sulfide composite material (FeCoS@rGO) synthesized in the present invention has higher specific capacity, better reversibility and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 FeCoS prepared in Example 1 4 XRD pattern of @rGO material.

[0026] Figure 2 FeCoS prepared in Example 1 4 Raman graph of @rGO material.

[0027] Figure 3 FeCoS prepared in Example 1 4 Scanning electron microscope (SEM) image of @rGO material.

[0028] Figure 4 FeCoS prepared in Example 1 4 Transmission electron microscope TEM image of @rGO material.

[0029] Figure 5 FeCoS prepared in Example 1 4 XPS energy spectra of different valence bond orbitals of @rGO materials.

[0030] Figure 6 FeCoS prepared in Example 1 4 High-resolution XPS spectrum of Fe element of @rGO material.

[0031] Figure 7 FeCoS prepared in Example 1 4 High-resolution XPS spectrum of Co element in @rGO material.

[0032] Figure 8 The FeCoS coated with graphene without oxide prepared in Example 1 4 Thermogravimetric (TG) curve of the material.

[0033] Fig. 9 FeCoS prepared in Example 1 4 @rGO material as a negative electrode for potassium ion batteries at a current density of 50 mA / g.

[0034] Fig.10 FeCoS prepared in Example 1 4 Rate performance curve of @rGO material as anode of potassium ion battery. DETAILED DESCRIPTION

[0035] This patent relates to a method for preparing a graphene oxide-coated dual transition metal composite electrode material and its application in the negative electrode of potassium ion batteries. The experimental technical scheme of the present invention will be further described in detail in conjunction with the accompanying drawings and the following specific embodiments. The examples cited are only used to explain the present invention, do not include all embodiments of the present invention, and are not used to limit the scope of the present invention.

[0036] Embodiment 1:

[0037] (1) 50 mg of graphene oxide was dissolved in 45 ml of deionized water and ultrasonically dispersed for 2 h. 5 ml of ammonia water was dropped into the graphene dispersion at room temperature and stirred at 600 rpm / min for 10 min.

[0038] (2) 1 mmol of CoCl 2 6H 2 O and 1 mmol FeCl 3 6H 2 O is dissolved in the mixed solution. The round-bottom flask is stirred in an oil bath at 90°C for 4 h at a speed of 500 rpm / min. After the reaction is completed, it is washed with deionized water and ethanol until neutral, and dried in an electric heating blast drying oven to obtain a black powder precursor for use;

[0039] (3) The black product precursor and sublimed sulfur were mixed and ground evenly in a mass ratio of 1:1, placed in a porcelain boat, and heat treated at 155°C for 1 h in an argon atmosphere, then continued to heat to 450°C and calcined for 2 h. After natural cooling, the reduced graphene oxide-coated double transition metal sulfide composite material FeCoS was obtained. 4 @rGO.

[0040] Embodiment 2:

[0041] (1) 37.5 mg of graphene oxide was dissolved in 45 ml of deionized water and ultrasonically dispersed for 2 h. 5 ml of ammonia water was dropped into the graphene dispersion at room temperature and stirred at 600 rpm / min for 10 min.

[0042] (2) 1 mmol of CoCl 2 6H 2 O and 1 mmol FeCl 3 6H 2 O is dissolved in the mixed solution. The round-bottom flask is stirred in an oil bath at 90°C for 4 h at a speed of 500 rpm / min. After the reaction is completed, it is washed with deionized water and ethanol until neutral, and dried in an electric heating blast drying oven to obtain a black powder precursor for use;

[0043] (3) The black product precursor and sublimed sulfur were mixed and ground evenly in a mass ratio of 1:1, placed in a porcelain boat, and heat treated at 155°C for 1 h in an argon atmosphere, then continued to heat to 550°C and calcined for 2 h. After natural cooling, the reduced graphene oxide-coated double transition metal sulfide composite material FeCoS was obtained. 4 / FeCoS 2 @rGO.

[0044] Embodiment 3:

[0045] (1) 25 mg of graphene oxide was dissolved in 45 ml of deionized water and ultrasonically dispersed for 2 h. 5 ml of ammonia water was dropped into the graphene dispersion at room temperature and stirred at 600 rpm / min for 10 min.

[0046] (2) 1 mmol of CoCl 2 6H 2 O and 1 mmol FeCl 3 6H 2 O is dissolved in the mixed solution. The round-bottom flask is stirred in an oil bath at 90°C for 4 h at a speed of 500 rpm / min. After the reaction is completed, it is washed with deionized water and ethanol until neutral, and dried in an electric heating blast drying oven to obtain a black powder precursor for use;

[0047] (3) The black product precursor and sublimed sulfur were mixed and ground evenly in a mass ratio of 1:1, placed in a porcelain boat, and heat treated at 155°C for 1 h in an argon atmosphere, then continued to heat to 650°C and calcined for 2 h. After natural cooling, the reduced graphene oxide-coated double transition metal sulfide composite material FeCoS was obtained. 2 @rGO.

[0048] The electrode materials obtained above were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS).

[0049] Figure 1 FeCoS prepared in Example 1 4 XRD pattern of @rGO material. It can be seen from the figure that the composite material has obvious FeCoS 4 Diffraction peaks indicate that the synthesized material is FeCoS 4 No characteristic peak of reduced graphene oxide was observed, indicating that the content of reduced graphene oxide was low.

[0050] Figure 2 FeCoS prepared in Example 1 4 Raman graph of @rGO material. The results in the figure show that reduced graphene oxide exists in the composite material, proving that FeCoS 4Successful preparation of @rGO.

[0051] Figure 3 FeCoS prepared in Example 1 4 SEM image of @rGO. It can be seen that FeCoS 4 Uniformly composited with reduced graphene oxide.

[0052] Figure 4 FeCoS prepared in Example 1 4 TEM image of @rGO. It can be seen that FeCoS 4 The nanoparticles are uniform in size.

[0053] Figure 5 FeCoS prepared in Example 1 4 XPS spectra of different valence bond orbitals of @rGO. Further evidence that FeCoS 4 The successful synthesis of @rGO and further confirmation of the valence state distribution of the composite material.

[0054] Figure 6 FeCoS prepared in Example 1 4 High-resolution XPS spectrum of Fe element of @rGO. The peaks at 707.4 and 720.3 eV in the figure are Fe 2+ characteristic peaks, while the peaks at 711.1 and 724.5 eV correspond to Fe 3+ .

[0055] Figure 7 FeCoS prepared in Example 1 4 High-resolution XPS spectrum of Co element of @rGO. The positions at 778.9 and 794.5 eV correspond to Co 2+ , the peaks at 782.1 and 798.3 eV correspond to Co 3+ .

[0056] Figure 8 FeCoS prepared in Example 1 4 Thermogravimetric curve of FeCoS in nitrogen atmosphere. 4 It starts to decompose at 400℃, and the decomposition rate decreases after 600℃, and the phase structure gradually stabilizes. This result provides a basis for regulating the phase of bimetallic sulfides.

[0057] The bimetallic sulfide FeCoS coated with reduced graphene oxide prepared in Example 1 4 @rGO is a sample of negative electrode material for potassium ion battery. The electrochemical performance test is carried out as follows:

[0058] FeCoS 4The @rGO composite material, Ketjen black (C600JD) and binder (CMC) were mixed and ground in a mass ratio of 7:2:1, and deionized water and anhydrous ethanol were added and stirred for more than 8 hours to prepare a slurry. The obtained slurry was coated on the copper foil by a doctor blade method and dried at 60°C for 12 hours. The average loading amount was 0.8-1 mg / cm 2 . Then it was assembled with a potassium metal sheet into a button half-cell for electrochemical performance testing.

[0059] Fig. 9 FeCoS 4 @rGO electrode cycle performance test diagram. At a current density of 50mA / g, the first discharge capacity reached 1616.6mAh / g, the charge capacity was 604.6mAh / g, and the first coulombic efficiency reached 37.4%. After 45 cycles, its reversible capacity was still 479.5mAh / g, showing excellent cycle performance.

[0060] Fig.10 FeCoS 4 @rGO potassium ion battery negative electrode rate performance charge and discharge curve. At a current density of 50mA / g, the reversible specific capacity is 529mAh / g. When the current density gradually increases to 500mA / g, the reversible specific capacity is 166mAh / g, which is about 31% of the current density of 50mA / g. When the current density returns to 50mA / g, the reversible specific capacity returns to 517mAh / g, showing excellent rate performance.

[0061] The above is a preferred embodiment of the present invention and does not limit the present invention in any form. Any modification, equivalent replacement, improvement, etc. made within the scope of the technical solution of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a reduced graphene oxide-coated double transition metal sulfide composite material, characterized in that: The steps include: (1) fully ultrasonically dispersing graphene oxide in deionized water, and adding ammonia water to form an alkaline environment; obtaining a graphene oxide dispersion; the concentration of the graphene oxide dispersion is 0.5-1 mg / mL, and the volume ratio of ammonia water to deionized water is 1:9; wherein the ultrasonication time is 2 h; (2) fully dissolving the iron salt and the cobalt salt in the graphene oxide dispersion, stirring at a certain temperature for a certain period of time, washing with deionized water and ethanol by centrifugation until neutral, and drying in an electric heating blast drying oven to obtain a black powder product precursor FeCoO for standby use; (3) The black product precursor FeCoO and sublimed sulfur are mixed and ground evenly according to a certain proportion, placed in a porcelain boat, and heat treated at 140-170°C for 1-2 hours under a protective gas atmosphere, and then continued to heat to 350-650°C at a rate of 5°C / min and calcine for 2-3 hours to finally obtain a double transition metal sulfide composite material FeCoS4@rGO coated with reduced graphene oxide; Reduced graphene oxide-coated double transition metal sulfide composite FeCoS4@rGO for potassium ion battery anode; The mass ratio of the black product precursor to the sublimated sulfur is 1:0.5-1:

4.

2. The preparation method according to claim 1, characterized in that In step (2), the total concentration of metal salts in the graphene oxide dispersion is 0.04 mol / L, wherein the molar ratio of Fe to Co is 1:

1.

3. The preparation method according to claim 1, characterized in that: In step (2), the stirring temperature is 80-100° C. and the stirring time is 4 h.

4. Use of the reduced graphene oxide-coated double transition metal sulfide composite material prepared by the preparation method according to any one of claims 1 to 3 as a negative electrode of a potassium ion battery.

Citation Information

Patent Citations

  • Elemental sulfur-rich nickel-cobalt sulfide and graphene composite material preparation method

    CN111573745A

  • Research of antimony-based composite metal sulfide as negative electrode material of potassium ion battery

    CN112002893A